Optimal techno-economic-environmental study of using renewable energy resources for Yanbu city - Alghamdi, Osama A.; Alhussainy, Abdullah Ali; Alghamdi, Sultan; AboRas, Kareem M.; Rawa, Muhyaddin; Abusorrah, Abdullah M.; Alturki, Yusuf A. (Frontiers in Energy Research, 2023)
The world’s attention is increasingly focused on the growing need to diversify energy sources. Saudi Arabia is under natural pressure to seize the opportunity in the renewable energy sector. Since renewable natural resources such as wind and solar energy are less expensive and environmentally friendly, most countries like to move away from the use of fossil fuels. This paper focuses on a techno-economic-environmental study of supplying Yanbu city in Saudi Arabia with a hybrid energy system consisting of solar energy, wind energy, and storage batteries. This has been carried out by considering an off-grid system or a system connected to the grid. In order to find the best solution from technical, economic, and environmental perspectives to supply the city, 15 options were considered. Photovoltaic (PV) and wind turbines (WT) connected to a grid make up the grid-connected system. The off-grid system considers the development of a load profile for Yanbu city. In both systems, an energy storage system (ESS) is essential (off-grid and grid-connected). The results show that the 850-MW PV system connected to the grid without an ESS is the best option both economically and technically.